Moderating variables of music training-induced neuroplasticity: a review and discussion - Merrett, Dawn L.; Peretz, Isabelle; Wilson, Sarah J. (Frontiers in Psychology, 2013)
A large body of literature now exists to substantiate the long-held idea that musicians' brains differ structurally and functionally from nonmusicians' brains. These differences include changes in volume, morphology, density, connectivity, and function across many regions of the brain. In addition to the extensive literature that investigates these differences cross-sectionally by comparing musicians and nonmusicians, longitudinal studies have demonstrated the causal influence of music training on the brain across the lifespan. However, there is a large degree of inconsistency in the findings, with discordance between studies, laboratories, and techniques. A review of this literature highlights a number of variables that appear to moderate the relationship between music training and brain structure and function. These include age at commencement of training, sex, absolute pitch, type of training, and instrument of training. These moderating variables may account for previously unexplained discrepancies in the existing literature, and we propose that future studies carefully consider research designs and methodologies that control for these variables.